Implementasi Circular Economy Berbasis Maqashid Syariah Dalam Menghadapi Krisis Perubahan Iklim Global - Adina Litriwani; Shafwatul Hilwa; Muhammad Ridho Efryanda (CV. KAMPUS AKADEMIK PUBLISING, 2026)
The global transition from the gold-backed Bretton Woods system to a fiat monetary system in 1971 marked a fundamental shift in the structure of the world economy and contributed to the emergence of the circular economy as an alternative to the linear economic model. Under the Bretton Woods framework, major currencies such as the British pound (GBP), the Indonesian rupiah (IDR), and several European currencies were relatively stable due to their linkage to gold. However, in practice, the implementation of the circular economy has often been approached primarily from a technical perspective, emphasizing efficiency and resource optimization while neglecting ethical, social, and spiritual dimensions. In this context, the principles of maqashid shariah—which aim to safeguard religion, life, intellect, progeny, and wealth—offer a normative and ethical foundation for promoting a more just and sustainable economic system. This article seeks to examine the role of maqashid shariah principles in advancing the concept of Green Sharia Business as a strategic framework to encourage the adoption of a circular economy in Indonesia. The concept of Green Sharia Business integrates Islamic ethical values with circular economy principles to support sustainable development.The government plays a crucial role in facilitating the implementation of this concept through the enforcement of environmentally oriented regulations, the provision of fiscal incentives such as tax benefits, and capacity-building programs for sharia-based business actors in adopting circular economy practices. Consequently, the integration of maqashid shariah and the circular economy is expected to foster an economic system that not only prioritizes financial performance but also ensures long-term social and environmental sustainability.